profile
Опубликовано 8 месяцев назад по предмету Алгебра от angelforever20

Упростите выражение:
(a-3b)(a+3b)-(a-3b)²
4x³*(-2x²)³
Помогите пожалуйста)

  1. Ответ
    Ответ дан Misha001192

    1)  (а - 3b)(a + 3b) - (a - 3b)² = a² - 9b² - (a² - 6ab + 9b²) = a² - 9b² - a² + 6ab - 9b² = - 18b² + 6ab

    2)  4x³ • ( - 2x² )³ = 4x³ • ( - 8x⁶ ) = 4 • (-8) • x³ • x⁶ = - 32x⁹

    ===========================================================

    (a - b)(a + b) = a² - b² --- разность квадратов

    (a - b)² = a² - 2ab + b² --- квадрат разности

Самые новые вопросы